The Stiffness of Steel-Wood-Steel Connection Loaded Parallel to the Grain - Nur Liza, Rahim; Raftery, Gary; Quenneville, Pierre; Doh, Shu Ing; Nabialek, Marcin; Putra Jaya, Ramadhansyah; Norlia, Mohamad Ibrahim; Mohd Mustafa Al Bakri, Abdullah; Śliwa, Agata (Polish Academy of Sciences, 2022)
In Eurocode 5, the stiffness equation for bolted steel-wood-steel is stated as a function of wood density and fastener diameter only. In this research, an experimental study on various configurations of tested bolted steel-wood-steel (SWS) connections has been undertaken to predict the initial stiffness of each connection. In order to validate the Eurocode 5 stiffness equation, tests on 50 timber specimens (40 glued laminated timbers and 10 laminated veneer lumbers (LVL)) with steel plates were undertaken. The number of bolts was kept similar and the connector diameter, timber thickness, and wood density were varied. The results obtained in the experimental tests are compared with those obtained from the Eurocode 5 stiffness equation. From the analysis, it is signified that the stiffness equation specified in Eurocode 5 for bolted SWS connections does not adequately predict the initial stiffness. The results from Eurocode 5 stiffness equation are very far from the experimental values. The ratio of stiffness equation to experimental results ranges from 3.48 to 4.20, with the average at 3.77, where the equation overpredicted the experimental stiffness value for the connection. There is a need to consider or incorporated other parameters such as geometric configurations in Eurocode 5 stiffness equation to improve the ratio with the experimental data.